Efficacy of open weave jute geotextiles in controlling soil erosion and its impact on hill slope stabilization - MANIVANNAN, S; KHOLA, O P S; KANNAN, K; CHOUDHURY, P K; THILAGAM, V KASTHURI (The Indian Journal of Agricultural Sciences, 2018)
Slope stabilization is a tedious process since various human activities being carried out in various parts of the world have led to land use changes that has indirectly affected slope stability. Permanent structures are being used for slope stabilization which are costly and cannot be adopted in a large scale. Slope stabilization by establishing grasses with the support of Jute Geotextiles is an alternative method for stabilization of slopes in hilly areas. Set of field studies were conducted at ICAR- Indian Institute of Soil and Water Conservation (IISWC), Regional Centre, Udhagamandalam, Tamil Nadu, India with the objective to study the effect of various Jute Geotextiles (JGT) on runoff, soil loss, survival and growth of tea. Results of three years field study on efficacy of various types of open weave JGT namely 500, 600 and 700 GSM on slope stabilization showed that 700 GSM open weave JGT proved to be more effective in reducing runoff, soil and nutrient loss and increased soil moisture retention capacity of the soil. However, height and growth of tea plants were better under 500 and 600 GSM JGT. Considering the scope of tea cultivation in sloppy areas, rehabilitation of land slide areas using tea plants, optimal moisture requirement and better growth of tea plants, it is suggested that 500 GSM open weave JGT will be more effective for slope stabilization with tea plants.